Предмет: Алгебра,
автор: helppil
сократить дробь: (a^4-3a^2+1)/((3a^2+3a-3)^2)
Приложения:
Ответы
Автор ответа:
0
Преобразуем Числитель:
a^4 - 3a^2 + 1 = a^4 - 2a^2 + 1 - a^2 = (a^2 - 1)^2 - a^2 =
= (a^2 + a - 1)(a^2 - a - 1)
Преобразуем Знаменатель:
(3a^2 + 3a - 3)^2 = (3*(a^2 + a - 1))^2 = 9 (a^2 + a - 1)^2
Находим отношение числитель/знаменатель, в котором уже есть что сокращать:
(a^2 + a - 1)*(a^2 - a - 1) a^2 - a - 1
--------------------------------- = -------------------
9*(a^2 + a - 1)^2 9*(a^2 +a - 1)
a^4 - 3a^2 + 1 = a^4 - 2a^2 + 1 - a^2 = (a^2 - 1)^2 - a^2 =
= (a^2 + a - 1)(a^2 - a - 1)
Преобразуем Знаменатель:
(3a^2 + 3a - 3)^2 = (3*(a^2 + a - 1))^2 = 9 (a^2 + a - 1)^2
Находим отношение числитель/знаменатель, в котором уже есть что сокращать:
(a^2 + a - 1)*(a^2 - a - 1) a^2 - a - 1
--------------------------------- = -------------------
9*(a^2 + a - 1)^2 9*(a^2 +a - 1)
Автор ответа:
0
спасибо большое!
Похожие вопросы
Предмет: Химия,
автор: Аноним
Предмет: Английский язык,
автор: gobniktona
Предмет: Математика,
автор: stepanmuravev200830
Предмет: Литература,
автор: Снежочек2
Предмет: Математика,
автор: evgenkosar